Planning Decision Support System Using Building Mall A`HP (Analytical Hierarchy Process) - Rizki Amarullah; R. Mahdalena Simanjorang (Jurnal Teknik Informatika C.I.T Medicom, 2020)
The development of information systems and technology today plays an important role and are very useful in various fields covering all aspects of human life. One of the beneficiaries of the computer and information technology systems in the aspect of human life is in helping determine a decision. PT. Karsa Prima Permata Nusa (KPPN) is a company engaged in the contracting business. In the exercise of business at. KPPN still using manual estimates. As a result of that often appear in this condition is takes a long time to determine the location for a development taking into account the requirements-requirements that already ditentukan.dengan location desired, other than that decisions are rendered ineffective because after the construction of walking occur some problems that do not fit the expected results. One method is a decision support system AHP (Analytical Hierarchy Process). AHP (Analytical Hierarchy Process) is a model of decision support system will spell trouble multi-factor or multi-criteria complex into a hierarchy, the hierarchy is defined as a representation of a complex problem in a structure of interest, which follow the level of the factors, criteria, and so on down to the last level.